Recuperação judicial de grupo de sociedades: a consolidação e sua aplicação no direito brasileiro - Laura Sarti Mozelli (2017)
The purpose of this work is to analyze the reorganization of a group of companies focusing on substantial consolidation, a concept coined by US jurisprudence and adopted by the UNCITRAL model law on insolvency. Although the institute is not new, its discussion in the Brazilian Courts is current and related to the repercussions of the global economic crisis of 2008 and, more recently, to the political-economic crisis that the country is going through. For the development of the study, the structure of Law n 11.101/05 was analyzed, especially its principles and to whom it applies; the concept and types of corporate groups have been taken up briefly; it was examined the disregard of the legal personality and its application in the groups and, without intending to make a study of comparative law, outlined, from the study of foreign doctrine on the subject, a brief overview of the emergence and evolution of consolidation in the North American jurisprudence. A jurisprudence research was carried out by the Courts of Minas Gerais, Rio de Janeiro and São Paulo on the subject in order to verify the employment, although intuitive, of the substantive consolidation in Brazilian law. The analysis of the decisions made it possible to identify the grounds invoked for the application of consolidation, as well as controversial issues, such as the presentation of the list of creditors and the reorganization plan, the form and voting quorum of the plan and the consequences of the approval or rejection of the substantive consolidation.